2017
DOI: 10.5435/jaaosglobal-d-17-00048
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Open Reduction and Internal Fixation Versus Closed Reduction and Percutaneous Fixation for Medial Malleolus Fractures

Abstract: Introduction:Surgical treatment of medial malleolus (MM) fractures can be performed through open or percutaneous approaches, although comparisons between these two approaches have not been undertaken. In this study, we compared patients with MM fractures treated with closed reduction and percutaneous fixation (CRPF) with patients treated with traditional open reduction and internal fixation (ORIF).Methods:A group of 165 consecutive patients underwent surgical fixation of a closed MM fracture from 2011 to 2015 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
2
6
1
Order By: Relevance
“…In the comparative study conducted by Matson et al (2017), forty patients with ankle fractures were treated by percutaneous fixation and achieved a mean duration of union within 10± 4 weeks, which is delayed in comparison to our results [8]. In the previous study, another group of 144 patients were treated by tension band wiring and achieved a mean duration of union within 10± 11 weeks [8]. In comparison to the results of Matson et al (2017), our results revealed that the union rate was faster.…”
Section: Discussioncontrasting
confidence: 64%
“…In the comparative study conducted by Matson et al (2017), forty patients with ankle fractures were treated by percutaneous fixation and achieved a mean duration of union within 10± 4 weeks, which is delayed in comparison to our results [8]. In the previous study, another group of 144 patients were treated by tension band wiring and achieved a mean duration of union within 10± 11 weeks [8]. In comparison to the results of Matson et al (2017), our results revealed that the union rate was faster.…”
Section: Discussioncontrasting
confidence: 64%
“…In our study, cannulated cancellous screw was used in 62.69% cases and tension band wiring was used in 37.31% compared with Ebraheim et al 14 study in which overall screws were used in 58.58%, tension band wiring construct used in 27.92%, plate in 6.3%, and Kirschner-wires in 7.2%. Based on fracture pattern, overall transverse fracture pattern was more that constituted 58%, compared with Ebraheim et al's study 14 and Andrew et al's study 15 where in transverse fracture accounted 75 and 58.58%, respectively.…”
Section: Discussionmentioning
confidence: 59%
“…18 This approach is similar to the standard technique for open medial malleolar fixation, likely with similar risks. 19,20 Our proposed technique describes creating a medial transmalleolar portal, thereby granting access to these hard-to-reach areas of the talus without performing a medial osteotomy. This technique also circumvents the need for extensive soft tissue dissection and avoids potential complications associated with open techniques.…”
Section: Pearls Pitfallsmentioning
confidence: 99%
“…This technique also circumvents the need for extensive soft tissue dissection and avoids potential complications associated with open techniques. 11,17,19,20 Fixation of talus OCD with screws is ideal for nondisplaced or minimally displaced lesions with intact cartilage. 21,22 Other techniques such osteochondral autograft may be possible through the medial transmalleolar portal.…”
Section: Pearls Pitfallsmentioning
confidence: 99%